Personality Disorders in Persons with Gender Identity Disorder. (13th May 2014) - Duišin, Dragana; Batinić, Borjanka; Barišić, Jasmina; Djordjevic, Miroslav L.; Vujović, Svetlana; Bizic, Marta
Abstract : Background. Investigations in the field of gender identity disorder (GID) have been mostly related to psychiatric comorbidity and severe psychiatric disorders, but have focused less on personality and personality disorders (PDs). Aims. The aim of the study was to assess the presence of PDs in persons with GID as compared to cisgendered (a cisgender person is a person who is content to remain the gender they were assigned at birth) heterosexuals, as well as to biological sex. Methods. The study sample consisted of 30 persons with GID and 30 cisgendered heterosexuals from the general population. The assessment of PDs was conducted by application of the self-administered Structured Clinical Interview for DSM-IV Axis II PDs (SCID-II). Results. Persons with GID compared to cisgender heterosexuals have higher presence of PDs, particularly Paranoid PD, avoidant PDs, and comorbid PDs. In addition, MtF (transwomen are people assigned male at birth who identify as women) persons are characterized by a more severe psychopathological profile. Conclusions. Assessment of PDs in persons with GID is of great importance as it comprises a key part of personalized treatment plan tailoring, as well as a prognostic factor for sex-reassignment surgery (SRS) outcome.